2017
DOI: 10.1038/s41598-017-00128-5
|View full text |Cite
|
Sign up to set email alerts
|

Addressing rainfall data selection uncertainty using connections between rainfall and streamflow

Abstract: Studies of the hydroclimate at regional scales rely on spatial rainfall data products, derived from remotely-sensed (RS) and in-situ (IS, rain gauge) observations. Because regional rainfall cannot be directly measured, spatial data products are biased. These biases pose a source of uncertainty in environmental analyses, attributable to the choices made by data-users in selecting a representation of rainfall. We use the rainforest-savanna transition region in Brazil to show differences in the statistics describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…Global gridded P products are typically much coarser than those available in North America and Europe and coarser than the MODIS-derived SP. These products are Water Resources Research 10.1002/2017WR021899 modeled and interpolated from station, radar and satellite data and can have considerable uncertainties (Bosilovich et al, 2008;Fekete et al, 2004;Kidd et al, 2012;Levy et al, 2017;Schamm et al, 2014) with heightened uncertainty of over 100% in high latitude and topographically complex areas including the Rocky Mountains, Tibetan Plateau, and Andes (Saavedra et al, 2018;Tian & Peters-Lidard, 2010).…”
Section: Applications Using Sp To Predict Streamflowmentioning
confidence: 99%
“…Global gridded P products are typically much coarser than those available in North America and Europe and coarser than the MODIS-derived SP. These products are Water Resources Research 10.1002/2017WR021899 modeled and interpolated from station, radar and satellite data and can have considerable uncertainties (Bosilovich et al, 2008;Fekete et al, 2004;Kidd et al, 2012;Levy et al, 2017;Schamm et al, 2014) with heightened uncertainty of over 100% in high latitude and topographically complex areas including the Rocky Mountains, Tibetan Plateau, and Andes (Saavedra et al, 2018;Tian & Peters-Lidard, 2010).…”
Section: Applications Using Sp To Predict Streamflowmentioning
confidence: 99%
“…Generally, the seasonality follows the variation in maximum solar heating, but other factors, such as ocean thermal inertia, topography, dynamics and circulation, moisture transport, and the state of the land surface, can exert considerable influence on the timing and amplitude of tropical land region seasonal evolution. Over the Amazon Basin, seasonality exhibits marked variation in both latitude and longitude: for example, at 5 • S, the dry-towet transition proceeds from the central Amazon eastward toward the Atlantic coast (Liebmann and Marengo, 2001). It is also worth noting a pervasive tendency for the dry-to-wet season transition to occur much more rapidly than the wetto-dry transition, as evident in tropical monsoon systems including South Asia, West Africa, and South America.…”
Section: Land-atmosphere Interactions and Their Impact On Tropical Sementioning
confidence: 99%
“…However, these authors also underscore the participation of the large-scale circulation and its role in establishing a background environment (e.g., moisture convergence) to support wet-season rainfall. Incursion of cold fronts into the southern Amazon may act as triggers for rapid initiation of wet-season onset once the local thermodynamics become favorable (Li et al, 2006).…”
Section: Land-atmosphere Interactions and Their Impact On Tropical Sementioning
confidence: 99%
“…Although CRU data have been previously used as the observed data set of comparison in regional climate studies over Brazil (Da Rocha et al, 2015;Lee & Berbery, 2012), because there exists poor station data coverage in the interior of South America our "observed" data set may be biased and underestimate spatial and interannual variability (Malhi & Wright, 2004;New et al, 1999). In an analysis comparing various gridded precipitation data sets, including CRU, to Agencia Nacional de Aguas streamflow data, Levy et al (2017) demonstrated that over the Brazilian rainforest-savanna transition zone, which overlaps with our study region, the Precipitation Estimate from Remotely Sensed Information using Artificial Neural Networks (PERSIANN) data set is the best observational data set for the region. In comparing the CRU data set to the PERSIANN data set, we find that the CRU data set closely aligns with the PERSIANN data set in Bahia, Piauí, Maranhão region, and Goiás and southwestern Mato Grosso ( Figure S4).…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 99%